THE BIOLOGY OF CANADIAN WEEDS: 20. Cornus canadensis L. - HALL, IVAN V.; SIBLEY, JACK D. (Canadian Journal of Plant Science, 1976)
Cornus canadensis L., bunchberry (Cornaceae), is a widespread, native herbaceous species generally growing in the litter under forest species or in the open where the climate is generally moist and cool. It occurs as a weed in lowbush blueberry fields recently developed from woodland. Cornus canadensis has been confused with Cornus suecica L. which it resembles. The two species grow side by side in Greenland, along the northern seacoasts of Eastern and Western Canada, and Alaska. The flesh of the fruit of C. canadensis is edible when cooked, but the berries with their stone-like seeds are unacceptable in the pack of frozen lowbush blueberry fruit. As C. canadensis is somewhat resistant to 2,4-D (2,4-dichlorophenoxyacetic acid), no chemical control is available at present for this species.